Hydrophobic and hydrophilic drug loading capacity of micro diatom frustule from diatomite - Le , Thi Duy Hanh (Journal of Technical Education Science, 2021)
The aim of this work was to strengthen the evidence of using micro diatom frustule as a promising candidate for drug loading materials for both hydrophobic and hydrophilic drug models. The morphological, surface elemental composition of diatomite powder, a raw source of micro diatom frustules and purified diatomite to collect micro diatom frustule were investigated. Scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS) confirmed again the porous silica structure of micro diatom structure as well as validated a necessity of raw diatomite purification before using. UV- vis was used to measure drug loading content of untreated and treated surface of micro diatom frustule with maximum loading for hydrophobic and hydrophilic drugs after 24 hours were at 5.48 ± 0.42% and 5.70 ± 0.34, respectively. Moreover, we also proved that the ability of drug adsorption on materials surface by the reduction of specific surface area and pore size of micro diatom frustule after loading using a (Brunauer–Emmett–Teller) BET method. Besides, the hydrophobic loading capacity of materials was affected by surface modification. Based on the results, micro diatom frustule showed a potential for a drug delivery system.